Characteristics of the catalytic fast pyrolysis of vegetable oil soapstock for hydrocarbon-rich fuel. (1st June 2020) - Wang, Yunpu; Ke, Linyao; Peng, Yujie; Yang, Qi; Du, Zhenyi; Dai, Leilei; Zhou, Nan; Liu, Yuhuan; Fu, Guiming; Ruan, Roger; Xia, Donghua; Jiang, Li
Graphical abstract: Highlights: Catalytic conversion of soapstock over HZSM-5 was conducted to produce aromatics. Effect of unsaturation degree on product distribution and composition was studied. The pyrolysis mechanism of soapstock and fatty acid salt over HZSM-5 was proposed. Abstract: Hydrocarbon-rich fuel from vegetable oil soapstock is potentially a good alternative to conventional fossil-derived fuels. This paper reported on pyrolysis experiments with compounds including vegetable oil soapstock, sodium stearate(C18), sodium palmitate(C16), sodium oleate(C18:1), and sodium linoleate(C18:2). The effects of pyrolysis temperature, HZSM-5 catalyst, unsaturation degree and carbon chain length on the formation of aromatic hydrocarbons were explored. Experimental results indicated that the relative content of oxygenated compounds significantly decreased in the condensable organic compounds of soapstock pyrolysis, and aromatic hydrocarbons increased when the HZSM-5 catalyst was used, in which toluene and xylene had the highest relative selectivity. High catalytic pyrolysis temperature was beneficial to the relative selectivity of benzene and toluene, but inhibited the relative selectivity of xylene and ethylbenzene. The increase in saturation of fatty acid salts promoted the reaction toward the production of polycyclic aromatic hydrocarbons, which were a kind of typical precursor of catalyst coking deactivation and carcinogenic pollutants.